(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The Covid-19 pandemic is currently a major challenge around the world. Getting and maintaining proper nutrition is essential to fight viruses. Nutrition is an integral part of the human immune system. Diet has a direct impact on people health, and a healthy diet will give their body the strength to fight the COVID-19 pandemic. But it’s hard to believe that a superfood can simply boost immunity. By including foods rich in micronutrients, people can have a healthy and nutritious diet. Certain nutrients such as vitamin C, vitamin D, vitamin E, vitamin B-6, folic acid, zinc, selenium, iron and protein support the vital growth of good bacteria